Structural changes in spinal cord neurons after low-intensity SHF-irradiation - Smoliarenko, I K; Shugurov, O O (Radiat͡s︡ionnai͡a︡ biologii͡a︡, radioėkologii͡a, 2009)
On anaesthetized cats carried out local irradiation by super high frequence waves (SHF) on spinal cord (SC) at a level L6-S1 of segments (lambda = 3 sm, power from 1 up to 3 mWt/sm2, time of an exposition--20 or 30 minutes). The sections of a brain painted with application of hematoxylin-eosin. The received images was studied on light microscope and were analyzed on the computer. On motho- and interneurones SC it is revealed, that such parameters as nucleus--cytoplasm relation and relation of volume of cytoplasm to surface of a nucleus are subject to the greatest influence. The effect of application are maximal during the small period after an irradiation (1-2 hours). Received results can testify on change of character of processes of a metabolism between a nucleus and cytoplasm, infringement of creation of neurotransmitter and decreasing of membrane potential of nervous cells and axons.